Effect of pretilt-induced symmetry-breaking on the polarization distribution of polar nematic liquid crystals - Hirokazu Kamifuji; Kazuma Nakajima; Mahiro Nakase; Yuji Tsukamoto; Masanori Ozaki; Hirotsugu Kikuchi (Applied Physics Express)
It is known that the orientation characteristics of ferroelectric nematic liquid crystals (FNLCs) were completely different from those of paraelectric NLCs due to the presence of macroscopic polarization. Moreover, the conventional FNLC orientation is strongly dependent on the alignment film and alignment process. In this study, we focused on two key parameters given by the alignment process: pretilt and the fluorophilic/fluorophobic properties of the alignment film. We clarified that these parameters commonly affect the polarization orientation characteristics of FNLC under both the rubbing method and the photo-alignment method. Furthermore, we successfully achieved uniform vertical polarization orientation without an external field.